Chapter 13: Pharmacy Management (Pharmacy Essentials: A Compact Guide for Students and Practitioners, 2025)
AuthorDr. Syed Ansar Ahmed, Associate Professor, Department of Pharmaceutical Chemistry, Indira College of Pharmacy, VishnuPuri, Nanded, Maharashtra, IndiaAbstractPharmacy management combines business operations with clinical services to ensure organizational effectiveness while maintaining patient care quality. Inventory control balances medication availability against financial constraints through systematic approaches including ABC classification prioritizing high-value items, economic order quantity calculations optimizing purchase volumes, perpetual inventory systems tracking real-time stock levels, and vendor management strategies negotiating favorable terms while preventing stockouts of critical medications. Quality management systems establish frameworks for continuous improvement through defined quality metrics, regular performance evaluation, deviation management protocols, and implementation of corrective and preventive actions (CAPA), with structures including Plan-Do-Check-Act cycles and Lean Six Sigma methodologies minimizing error rates while enhancing operational efficiency. Staff training and development builds competent pharmacy teams through structured orientation programs, ongoing competency assessment, performance evaluation systems, career advancement pathways, and succession planning, with educational approaches spanning traditional instruction, simulation exercises, preceptor development, and interprofessional training opportunities that align with organizational goals and regulatory requirements. Financial management ensures pharmacy viability through revenue cycle optimization, third-party contract analysis, expense control measures, budget development processes, and financial performance monitoring using key metrics including prescription volume, gross margin, inventory turnover, labor costs, and various productivity indicators that guide resource allocation decisionsKeywords: Operational Efficiency; Resource Optimization; Performance Improvement; Workforce Development; Fiscal ResponsibilityVIEW PDF